(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
The integration of the Republic of Uzbekistan into the global framework of large-scale international assessments (LSIAs), marked by its inaugural participation in the Trends in International Mathematics and Science Study (TIMSS) 2023, represents a pivotal juncture in the nation’s educational trajectory. This report provides an exhaustive, multi-dimensional analysis of the TIMSS 2023 dataset to evaluate the efficacy of current teaching methodologies and school management strategies within the Uzbek context. Utilizing data from 64 participating countries, with a specific focus on high-performing systems such as Singapore and Japan, this study diagnoses critical systemic deficits in cognitive activation, inquiry-based learning, and instructional leadership. The findings reveal that while Uzbekistan has achieved commendable parity in school belonging and safety, student achievement in mathematics and science remains significantly below the international CenterPoint, particularly in the cognitive domains of "Applying" and "Reasoning." This performance gap is exacerbated by a prevalence of rote-memorization pedagogies and a school leadership model heavily skewed toward administrative compliance rather than instructional improvement. Drawing upon extensive psychometric data, context questionnaires, and national policy documents, this article proposes a strategic framework for the "New Uzbekistan" education reform agenda. It advocates for a transition to competency-based curricula, the institutionalization of inquiry-based science education (IBSE), and the redefinition of the school principal’s role from administrator to instructional leader. This manuscript is structured to meet the rigorous standards of Q1 and Q2 Scopus-indexed journals, contributing to the international discourse on educational development in transition economies.